Flavokawain a induces apoptosis in MCF-7 and MDA-MB231 and inhibits the metastatic process in vitro - Nadiah, Abu; M. Nadeem, Akhtar; Yeap, Swee Keong; Lim, Kian Lam; Ho, Wan Yong; Aimi Jamil, Zulfadli; Abdul Rahman, Omar; Mohd Roslan, Sulaiman; Mohd Puad, Abdullah; Noorjahan Banu, Alitheen (Public Library of Science, 2014)
The kava-kava plant (Piper methsyticum) is traditionally known as the pacific elixir by the pacific islanders for its role in a wide range of biological activities. The extract of the roots of this plant contains a variety of interesting molecules including Flavokawain A and this molecule is known to have anti-cancer properties. Breast cancer is still one of the leading diagnosed cancers in women today. The metastatic process is also very pertinent in the progression of tumorigenesis.